Implementing Open-Source LMS in Humanities and Social Sciences - Klindžić, Jasmin (Array, 2008)
The best practices presentation will describe the process of selection, testing, implementation and support of open-source learning management system (Moodle based solution) in a large, heterogeneous humanities and social sciences institution at the University of Zagreb, Croatia. The following issues are discussed: institutional background and organization structure ; social and organizational prerequisites ; LMS software key features ; hardware minimum requirements ; misconceptions ; obstacles (from both organizational and IT literacy points of view) ; involvement in open-source community. A brief case-study for the implementation is given, based on our experience.